Monosodium l‐glutamate‐obesity onset is associated with disruption of central control of the hypothalamic‐pituitary‐adrenal axis and autonomic nervous system. (21st April 2019) - Torrezan, Rosana; Malta, Ananda; de Souza Rodrigues, Willian do Nascimento; dos Santos, Annie Araújo Alves; Miranda, Rosiane Aparecida; Moura, Egberto Gaspar; Lisboa, Patrícia Cristina; de Freitas Mathias, Paulo Cezar
Abstract: The hypothalamic‐pituitary‐adrenal axis (HPA) exerts important catabolic peripheral effects and influences autonomic nervous system (ANS)‐mediated processes. Impaired negative‐feedback control or reduced HPA axis sensitivity and altered ANS activity appear to be associated with the development and maintenance of obesity. In the present study, we examined the hypothesis that the central HPA axis is dysregulated favouring ANS disbalance in monosodium l ‐glutamate (MSG)‐induced rat obesity. Glucose homeostasis, corticosterone, leptin and ANS electrical activity were evaluated. Adult MSG‐induced obese rats exhibited fasting hyperinsulinaemia, insulin resistance, glucose intolerance, hypercorticosteronaemia, hyperleptinaemia and altered ANS activity. A decrease in food intake was observed during corticotrophin‐releasing hormone (CRH) treatment in both control and MSG‐treated rats. By contrast, food intake was significantly elevated in control rats treated with dexamethasone (DEXA), whereas no alterations were observed following DEXA treatment in MSG‐induced obese rats. After DEXA injection, an increase in fasting insulin and glucose levels, associated with insulin resistance, was seen in both groups. As expected, there was a decrease of parasympathetic activity and an increase of sympathetic nervous activity in CRH‐treated control animals and the opposite effect was seen after DEXA treatment. By contrast, there was no effect on ANS activity in MSG‐rats treated with CRH or DEXA. In conclusion, impairment of the HPA axis can lead to disbalance of ANS activity in MSG‐treated rats, contributing to the establishment and maintenance of obesity.